Akibat Hukum Wanprestasi Dalam Perjanjian Jual Beli Tanah Dan Implikasinya Terhadap Konsumen Selaku Pihak Ketiga - Reza Azurma; Duwi Handoko (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2025)
This article examines the legal consequences of default (wanprestasi) in land sale and purchase agreements and its implications for consumers as third parties. Using a normative and case-based approach, this study analyzes judicial decisions from the District Court of Depok (No. 55/Pdt.G/2022/PN Dpk), the Bandung High Court (No. 204/PDT/2023/PT BDG), and the Supreme Court (No. 2134 K/Pdt/2024). The case demonstrates the complexity of legal relations between the landowner, initial buyer, and end-consumers (such as housing unit buyers), who are affected by the annulment of sale agreements. The analysis reveals that the initial buyer’s default, including failure to pay and use of empty checks, led the courts to invalidate the agreement and return the land title to the seller. Third parties such as notaries, the National Land Agency, and consumers are placed in legally vulnerable positions. The study emphasizes the necessity of preventive legal safeguards, including due diligence, explicit contractual clauses, and clear third-party liability management in land sale chains.